Knowledge, attitude and behaviour of women towards abnormal menstrual bleeding and its impact on quality of life - R. Bhatiyani, Binti; V. Dhumale, Shrikant; B., Pandeeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal menstrual bleeding has a major impact on a woman’s quality of life. Any intervention therefore should aim to improve this rather than focusing on the amount of menstrual blood loss. The aim of this study was to gain an in depth understanding of women’s current knowledge, attitudes and beliefs around abnormal menstrual bleeding. Also, to understand how it affects their lives, while identifying current misconceptions and gaps in knowledge and their expectations and attitudes towards the treatment so that treatment can address their most bothersome complaint. Methods: A total of 200 women, between 18-55 years of age, not on any hormonal treatment attending the gynaecology OPD at a tertiary care centre between Jan 2017 to May 2017 were interviewed by a questionnaire. Women who had undergone hysterectomy were excluded from the study. Results: Of the 200 women interviewed, 49 women felt that their bleeding was heavy and formed the heavy menstrual bleeding group (HMB) while 151 women who perceived their bleeding to be normal formed the normal bleeding group. In the (HMB) group, a significantly greater proportion of women identified their menstrual bleeding as being an inconvenience and a disruption to their lives. HMB also significantly affected their relationships, social life and productivity at work place. Conclusions: Despite its common occurrence, awareness and understanding of HMB and its treatment within the survey population was poor.